Sensitization of the crayfish lateral giant escape reaction - Krasne, FB (J Neurosci, 1986)
Most behavioral reactions that habituate can also be dishabituated by strong stimuli. In the best studied cases, dishabituation seems to be the result of an independent “sensitization” of the behavioral reaction that compensates for habituation without necessarily abolishing it. Crayfish lateral giant (LG) neuron-mediated escape reactions are one of the most fully analyzed behavioral reactions that are prone to habituation; however, sensitization/dishabituation of LG escape has not previously been reported. Here, the effect of strong AC shocks to head or abdomen on the ability of 0.1 msec “test” shocks to sensory roots innervating the tailfan to elicit an LG escape response was examined. Following single AC shocks, test shock threshold for eliciting LG escape reliably fell 5–80% and recovered over 15 min to 1 hr. When AC shocks and test shocks alternated at 90 sec intervals, test shock threshold rapidly dropped to an asymptote that was maintained as long as AC shocks were given (up to 2 hr); following such repeated AC shocks, recovery often required a number of hours but was complete within 24. Comparable sensitization is seen in the response of interneuron A, the largest of a set of sensory interneurons that links afferents to LGs. AC shocks (to either head or tail) no longer sensitize abdominal LG reflex circuitry if the nerve cord is severed between thorax and abdomen. Thus, sensitization appears to depend on a neurally conducted influence that arises in the rostral half of the animal. Pharmacological evidence suggests that octopamine may mediate the sensitization.